A Comparative Study into the Effectiveness of Personalized Advertising - Arlon, Guillaume P. (2011)
This study aims to provide a comparative study of the effectiveness of personalized advertising. It provides a definition of a new form of advertising and defines it as the creation of an independent existence capable of entering language, daydreams and intuitions (Lannon and Cooper, 1983); in which the advertisement provides an informational or a creative message (Lannon and Cooper, 1983; Stewart and Koslow, 1989; Bhat, 1998) to promote goods or services to an individual using personally identifying information about the individual such as name, e-mail address and/or personal information (Yu and Cude, 2009) in order to interact with the individual, to attract one’s attention, and to create a positive response toward the message, product and brand to motivate purchase. This study raised the issue that impact from personalized advertising and questions the potential effectiveness of personalized advertising compared to traditional billboard advertising and came with the conclusion that there are no differences between personalized advertising and traditional billboard advertising in the way respondents perceive the product and or brand, nor in the way consumers move toward purchase. However it has been observed that there are little differences in the liking of the advertisements, and respondents did not like personalized advertising as much as traditional billboard advertising. However, respondents exposed to personalized advertising provided higher responses regarding their feelings toward the message of the advertisement and it can be observed that respondents felt that the message was more targeted to them, with a clearer understanding; but not only respondents recognized themselves more in personalized advertising, they felt closer to the message and more implicated in what the advertisement had to say to them. The study has shown that personalized advertisements are more likely to enhance recall, persuasion and comprehension even if the consumers’ personal information becomes the primary point of distinction and thus focus of the advertisement rather than the product itself. Finally a distinction has been made regarding how brands can use advertising to position their brand on a market and to the eyes of the consumers. Three levels of brand positioning have been described: ‘functional’, ‘prestige’, and ‘personality expression’; and the study provides knowledge to brand managers and advertisers, and suggest that personalized advertisements with a prestige brand positioning message have shown to be more effective than traditional billboards advertisements. But it has also shown to be the most effective among personalized advertising as well. Moreover, the study demonstrated that personalized advertising diminish this non-marketing effect as consumers recognized themselves more in personalized advertisements. However, not in all levels of the brand positioning, but primarily in brands using a prestige brand positioning.